Anodic Oxidation Enabled Cation Leaching for Promoting Surface Reconstruction in Water Oxidation. (18th February 2021) - Duan, Yan; Lee, Jun Yan; Xi, Shibo; Sun, Yuanmiao; Ge, Jingjie; Ong, Samuel Jun Hoong; Chen, Yubo; Dou, Shuo; Meng, Fanxu; Diao, Caozheng; Fisher, Adrian C.; Wang, Xin; et al.
Abstract: A rational design for oxygen evolution reaction (OER) catalysts is pivotal to the overall efficiency of water electrolysis. Much work has been devoted to understanding cation leaching and surface reconstruction of very active electrocatalysts, but little on intentionally promoting the surface in a controlled fashion. We now report controllable anodic leaching of Cr in CoCr2 O4 by activating the pristine material at high potential, which enables the transformation of inactive spinel CoCr2 O4 into a highly active catalyst. The depletion of Cr and consumption of lattice oxygen facilitate surface defects and oxygen vacancies, exposing Co species to reconstruct into active Co oxyhydroxides differ from CoOOH. A novel mechanism with the evolution of tetrahedrally coordinated surface cation into octahedral configuration via non‐concerted proton‐electron transfer is proposed. This work shows the importance of controlled anodic potential in modifying the surface chemistry of electrocatalysts. Abstract : CoCr2 O4 activated at 1.7 V for 1.5 h (Act‐CoCr2 O4 ) exhibits better OER activity compared to IrO2 in alkaline solutions. Pristine CoCr2 O4 is originally inactive; activation (>1.56 V) promotes Cr leaching and lattice oxygen losses in CoCr2 O4, leaving the highly defective surface for Co species to reconstruct into octahedrally coordinated Co 3+–4+ oxyhydroxide.